2022
DOI: 10.1007/s40279-022-01727-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Substrate Oxidation During Submaximal Cycling: A Modelling Analysis

Abstract: Background Multiple factors influence substrate oxidation during exercise including exercise duration and intensity, sex, and dietary intake before and during exercise. However, the relative influence and interaction between these factors is unclear. Objectives Our aim was to investigate factors influencing the respiratory exchange ratio (RER) during continuous exercise and formulate multivariable regression models to determine which factors best explain R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 199 publications
(287 reference statements)
0
14
0
Order By: Relevance
“…Exercise was summed into daily totals for workout duration and training load, along with coded variables for modality of workout (e.g., swim, bike, run, strength, other) and if any training was performed in the fasted state. Because dietary protein and fat ingestion have minimal effects on substrate oxidation [24, 25], fasted training was defined as consuming < 5 g of carbohydrate in the 4-h pre-exercise window. For multiple exercise sessions in a single day, a weighted mean based on the duration of each session was used to calculate a single value for pre-exercise carbohydrate ingestion in grams.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise was summed into daily totals for workout duration and training load, along with coded variables for modality of workout (e.g., swim, bike, run, strength, other) and if any training was performed in the fasted state. Because dietary protein and fat ingestion have minimal effects on substrate oxidation [24, 25], fasted training was defined as consuming < 5 g of carbohydrate in the 4-h pre-exercise window. For multiple exercise sessions in a single day, a weighted mean based on the duration of each session was used to calculate a single value for pre-exercise carbohydrate ingestion in grams.…”
Section: Methodsmentioning
confidence: 99%
“…These data are very similar to those measured in recreational but well-trained runners who had adapted to the LCHF diet for 6 weeks (Prins et al, 2019;Prins et al, 2023b). While these rapid adaptations may be partially explained by elite-level fitness (Rothschild et al, 2022), recent analyses have demonstrated that respiratory quotient and substrate oxidation changes occur in 4 days in male endurance athletes on an isocaloric LCHF diet (Prins et al, 2019), within 7 days (Hall et al, 2016) and 14 days in moderately trained athletes (Cipryan et al, 2018) and overweight/obese subjects (Buga et al, 2021;Hall et al, 2021), as biochemical changes consistent with increase fat oxidation (i.e., reduced glucose and insulin load; increase Data: Mean ± SD. *p < 0.05, **p < 0.01, ***p < 0.001, significant difference between LCHF and HCLF.…”
Section: Substrate Oxidationmentioning
confidence: 99%
“…The most obvious candidate would be a significant change in blood insulin concentrations and action (glucose-lowering effect of insulin) since even at modest blood concentrations, insulin exerts powerful control over the rates of glucose ( Thiebaud et al, 1982 ) and fat oxidation ( Bonadonna et al, 1990 ; Campbell et al, 1992 ; Horowitz et al, 1997 ). In an attempt to understand other factors which influence substrate oxidation during exercise, Rothschild et al conducted a multivariable regression of 434 studies ( Rothschild et al, 2022 ). Exercise duration, dietary fat intake, age, VO 2 max, and percentage of type 1 muscle fiber all were associated with decreased RER, while dietary carbohydrate intake, exercise intensity, male sex, and carbohydrate intake before and during exercise increased RER.…”
Section: Low-carbohydrate High-fat Diets and The Crossover Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy source used by the body in which oxygen is consumed (VO2) and carbon dioxide is produced (VCO2) is measured by calorimetry (Brandi et al, 1997; Battezzati and Vigano’, 2001). The ratio of VCO2/VO2 calculates the RER, which estimates the respective contributions of fats and carbohydrates to energy production, enabling the calculation of total energy expenditure (Rothschild et al, 2022). The circadian rhythms, which directly influence tissue homeostasis, sleep regulation, behaviour, and metabolism, are closely linked to the ageing process (Basso et al 2016; Sato et al 2017, 2022; Kuintzle et al 2017; Welz and Benitah 2020).…”
Section: Introductionmentioning
confidence: 99%